Randomized, Placebo-Controlled Trial of Acetaminophen for the Reduction of Oxidative Injury in Severe Sepsis: The Acetaminophen for the Reduction of Oxidative Injury in Severe Sepsis Trial*. Issue 3 (March 2015) - Janz, David R.; Bastarache, Julie A.; Rice, Todd W.; Bernard, Gordon R.; Warren, Melissa A.; Wickersham, Nancy; Sills, Gillian; Oates, John A.; Roberts, L. Jackson; Ware, Lorraine B.
Abstract : Objectives: This trial evaluated the efficacy of acetaminophen in reducing oxidative injury, as measured by plasma F2 -isoprostanes, in adult patients with severe sepsis and detectable plasma cell-free hemoglobin. Design: Single-center, randomized, double-blind, placebo-controlled phase II trial. Setting: Medical ICU in a tertiary, academic medical center. Patients: Critically ill patients 18 years old or older with severe sepsis and detectable plasma cell-free hemoglobin. Interventions: Patients were randomized 1:1 to enteral acetaminophen 1 g every 6 hours for 3 days ( n = 18) or placebo ( n = 22) with the same dosing schedule and duration. Measurements and Main Results: F2 -Isoprostanes on study day 3, the primary outcome, did not differ between acetaminophen (30 pg/mL; interquartile range, 24–41) and placebo (36 pg/mL; interquartile range, 25–80; p = 0.35). However, F2 -isoprostanes were significantly reduced on study day 2 in the acetaminophen group (24 pg/mL; interquartile range, 19–36) when compared with placebo (36 pg/mL; interquartile range, 23–55; p = 0.047). Creatinine on study day 3, a secondary outcome, was significantly lower in the acetaminophen group (1.0 mg/dL; interquartile range, 0.6–1.4) when compared with that in the placebo (1.3 mg/dL; interquartile range, 0.83–2.0; p = 0.039). There was no statistically significant difference in hospital mortality (acetaminophen 5.6% vs placebo 18.2%; p = 0.355) or adverse events (aspartate aminotransferase or alanine aminotransferase > 400; acetaminophen 9.5% vs placebo 4.3%; p = 0.599). Conclusions: In adults with severe sepsis and detectable plasma cell-free hemoglobin, treatment with acetaminophen within 24 hours of ICU admission may reduce oxidative injury and improve renal function. Additional study is needed to confirm these findings and determine the effect of acetaminophen on patient-centered outcomes.